2023
DOI: 10.1111/ijfs.16428
|View full text |Cite
|
Sign up to set email alerts
|

The effect of date seed powder supplementation on glycaemic markers and lipid profile in women with overweight and obesity: a randomised controlled trial

Abstract: Objective: The aim of this randomized controlled trial (RCT) was to investigate the effect of date kernel on glycemic control, lipid pro le, and weight in women with overweight and obesity.Design: One hundred twenty-four women with overweight or obesity were randomly assigned to receive the date kernel supplement or placebo for 12 weeks. Serum HbA1c was measured by High-performance liquid chromatography (HPLC), and fasting plasma glucose and lipid pro les by enzyme-linked immunosorbent assay (ELISA) kits. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The present study indicated that consumption of DSP for 8 weeks significantly decreased HbA1c, insulin, HOMA-IR, and HOMA-B; in addition, QUICK increased in diabetic patients consuming DSP. Consistently, Hashemzadeh et al stated that 12-weeks administration of DSP supplements (200 mg twice a day) considerably reduced FPG and HbA1c levels in overweight and obese women suffering from type 2 diabetes [ 29 ]. Following the DSP consumption, the reduction in FPG was marginally significant and the reduction of HbA1c was not clinically relevant, which may be attributed to the duration of the intervention that could not show the beneficial changes in this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…The present study indicated that consumption of DSP for 8 weeks significantly decreased HbA1c, insulin, HOMA-IR, and HOMA-B; in addition, QUICK increased in diabetic patients consuming DSP. Consistently, Hashemzadeh et al stated that 12-weeks administration of DSP supplements (200 mg twice a day) considerably reduced FPG and HbA1c levels in overweight and obese women suffering from type 2 diabetes [ 29 ]. Following the DSP consumption, the reduction in FPG was marginally significant and the reduction of HbA1c was not clinically relevant, which may be attributed to the duration of the intervention that could not show the beneficial changes in this parameter.…”
Section: Discussionmentioning
confidence: 99%